KEPEMILIKAN INDIVIDU MENURUT ISLAM - Zaki, Muhammad (JURNAL ILMU SYARIAH, 2014)
Individual Ownership According to Islam. Islam has set the terms of ownership, whether public ownership, the individual and thestate. By law, individuals are entitled to have, enjoy, and transfer of wealth, but people also have a moral obligation to spend in his property. Permissibility of individual ownership is an attempt to achieve distributive justice in real terms, and maintaining a balance in economic matters. Ownership system in Islam has many different features and systems of capitalism and communism, because Islam provides a balance between the opposites can be overstated by both the School of Economics. Although Islam gives rights to individuals to possess wealth, but the state has the right to regulate the ownership of individual interventions with the provisions outlined by the Islamic shariah.